(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to identify the impact of investment on achieving sustainable development in public education departments in Tabuk. The study adopted a descriptive-analytical approach and used a simple random sampling method. The study sample consisted of 399 individuals working in public education departments in Tabuk. The study reached a set of results, including an average level of investment in education, as well as an average level of achieving sustainable development in public education departments in Tabuk. It also demonstrated a statistically significant impact of investment on achieving sustainable development in public education departments in Tabuk. The study recommended the need to issue and implement legislation and laws that encourage investment in the educational process, focus on integrating local community organizations and non-profit organizations into the educational process, and work to develop innovative financing strategies that contribute to providing adequate and sustainable financial support to schools and educational institutions. It also sought to strengthen the role of schools in promoting environmental and community awareness among teachers and students.